Pemanfaatan Talas Beneng (Xanthosoma undipes) Sebagai Alternatif Sumber Karbohidrat Dalam Penguatan Kerawanan Pangan - Avilia, Alma (Universitas Ahmad Dahlan, 2023)
Good food security conditions are characterized by the availability of sufficient food sources for households and individuals. One of the triggers for food insecurity is due to dependence on one type of source. The majority of the population in Indonesia still depends on carbohydrate sources, namely rice. The existence of food diversification, namely by processing taro beneng as a source of carbohydrates, provides an opportunity to reduce food insecurity. This study aims to utilize the potential of taro beneng as an alternative carbohydrate by using quantitative methods and Systematic Literature Review methods by identifying and interpreting existing case studies with relevant methods. Taro beneng can be processed into various kinds of processed snacks to processed noodles. The nutritional value obtained when taro beneng is processed into alternative carbohydrates, namely noodles is 5.02% protein, 4.43% fat, 1.97% crude fiber and 77.1% carbohydrates.Kondisi ketahanan pangan yang baik ditandai dengan tersedianya sumber pangan bagi rumah tangga dan individu secara cukup. Salah satu pemicu timbulnya kerawanan pangan karena adanya ketergantungan pada satu jenis sumber. Mayoritas penduduk di Indonesia masih bergantung pada sumber karbohidrat yakni beras. Adanya diversifikasi pangan yakni dengan mengolah talas beneng sebagai sumber karbohidrat memberikan peluang untuk mengurangi kerawanan pangan. Penelitian ini bertujuan untuk memanfaatkan potensi talas beneng sebagai alternatif karbohidrat dengan menggunakan metode kuantitatif dan metode Systematic Literature Review serta menafsirkan studi kasus yang ada dengan metode yang relevan. Talas beneng dapat diolah menjadi berbagai macam olahan cemilan sampai dengan olahan mie. Adapun nilai gizi yang diperoleh ketika talas beneng diolah menjadi alternatif karbohidrat yakni mie adalah karbohidrat 77%, lemak 4%, protein 5%, dan serat kasar 2%.